ChemInform Abstract: The Solid Solution Series (GeTe)x(LiSbTe2)2 (1 ≤ x ≤ 11) and the Thermoelectric Properties of (GeTe)11(LiSbTe2)2. Issue 50 (10th December 2013) - Schroeder, Thorsten; Schwarzmueller, Stefan; Stiewe, Christian; de Boor, Johannes; Hoelzel, Markus; Oeckler, Oliver
Abstract The title compounds (x = 1, 2, 3, 4, 5, 6, 11) and the x = 0 end‐member Li2Sb2Te4 are obtained from stoichiometric mixtures of the elements (Ar, 700 °C, 1 h) and characterized by powder X‐ray and neutron diffraction, and thermoelectric measurements.